WAYS OF DEVELOPING PEDAGOGICAL ABILITIES. CONCEPT OF COMMUNICATION. - Saidjonova , Dilshoda (Journal of Pedagogical and Philological Research, 2026)
This article highlights the concept of pedagogical ability, its significance in a teacher’s professional activity, and the ways of its formation. The essence of communicative ability, which is one of the main components of pedagogical skill, is revealed. The importance of organizing effective communication between teachers and students, speech culture, empathy, listening, and influencing skills in the process of pedagogical communication is analyzed. Self-analysis, reflection, practical exercises, and the use of innovative methods are shown as important factors in the development of pedagogical abilities.